Menganalisis Anggaran Untuk Penerimaan Pada Industri Surabaya - Renggo Ais Aprilian; Putri Citra Devi; Muhammad Yasin (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This journal aims to analyze the budget used to manage revenue in the industry. In today's competitive economic context, effective budget planning and management is essential for companies to achieve long-term success. This research uses an analytical approach and industry case studies to explore various aspects related to revenue budgeting, including planning, implementation, control, and evaluation.